Impregnated acetate gauze compared with lipido-colloid contact layer at dressing removal pain: a single-blind cross-over randomised control trial. (2nd February 2019) - Meaume, Sylvie; Thomas, Pierre; Truchetet, François; Celerier, Philippe; Becherel, Pierre-André; Teot, Luc; Bedane, Christophe
Abstract : Objective: To evaluate the performance of Jelonet Plus (JP) and UrgoTul (UT), assessing pain at dressing removal when managing acute or chronic wounds at granulation and epithelialisation stages. Methods: This was a randomised, multicentre, controlled single-blinded study using a cross-over design. Hospitalised and ambulatory patients presenting with non-infected acute or chronic wounds (at least 40% of wound area of ≤100cm 2 covered with granulation tissue) were randomly allocated to be treated with either JP or UT dressings applied according to a standardised local care procedure for two days. At the following visit, patients received the other dressing for a second 2-day period. Pain was evaluated after two days of dressing application and immediately after its removal using a 100mm Visual Analog Scale (VAS). A pain level >30mm was considered as clinically relevant. A lower limit of −12% was determined as the threshold necessary to demonstrate the non-inferiority of JP compared to UT. Results: For the 99 patients completing the study, a difference of 7.9% was observed in favour of JP (83.8% JP versus 75.9% UT) for pain immediately after dressing removal (VAS score < 30mm) with a confidence interval (CI) lower limit of −2.6%, demonstrating non-inferiority (pre-defined limit of −12%). Concerning pain at dressing removal, a difference of 19.6% was observed in favour of JP (81.6% versus 62.0%; p=0.029 for superiority analysis), with a CI lower limit ranging from 2.4% to 38.9%. Therefore, superiority could be concluded. A statistically significant period effect was detected (p=0.003) with fewer patients experiencing pain after the second period day 2 (D2) to day 4 (D4) than the first day 0 (D0) to D2. A statistically significant cross-over effect was also detected (p=0.047), with fewer patients experiencing pain when JP was applied first followed by UT. This suggests a carry-over effect thus preventing a full cross-over design analysis. Adherence of the dressing was less frequent with the JP than the UT dressing (2.0% JP versus 6.9% with UT). Conclusion: Non-inferiority of pain at dressing removal was demonstrated with JP. Superiority on this criteria was non-significant but we found adherence of the dressing to the wound bed to be more rare.